Landslide Susceptibility Analysis along the Mugling-Narayanghat Highway in Nepal - Regmi, Prakash (Rupantaran: A Multidisciplinary Journal, 2025)
This paper analyzes the landslide susceptibility of the Mugling-Narayanghat highway in Nepal. Nepal experiences annual landslide disasters, particularly along river corridors, causing frequent roadblocks and traffic jams during the monsoon season. The term landslide susceptibility refers to the likelihood of a landslide occurring in an area, influenced by terrain conditions. Mapping landslide susceptibility helps identify influential factors, estimate slope failure contributions, and establish associations between factors and landslides to predict future hazards. The Mugling-Narayanghat highway (MNH) is the busiest route connecting Kathmandu and Pokhara to the Indian border, serving over 6000 vehicles daily. The study was based on secondary data. The open sources digital data were taken from Google Earth Pro and Food and Agriculture Organization (FAO) published data. They were taken from different websites. And the collected data were analyzed into ARCMAP 10.8. There were nine different parameters were used to analyze landslide influence levels. This paper reveals that most of the road areas are to be considered vulnerable, and 18 points are to be identified as more vulnerable along the road in the study area.